GELIAT PEREMPUAN DI HOME INDUSTRI KERAJINAN GEDEBOG PISANG - Suji; Siti Makrufah; Rina Puji Rahmawati; Putri Aisyiyah Rachma Dewi (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
This study aims to describe the empowerment process through the banana stem craft home industry in Prambatan Village and its contribution to increasing the income of housewives. Using a descriptive qualitative approach, this study involved observation, interviews, and documentation of the owners and employees of UD. Barokah Tani. The results of the study indicate that this home industry has succeeded in empowering the community, especially women, through increased income and economic independence. The obstacles faced include limited production equipment, fluctuations in the availability of raw materials, and industry competition. This study concludes that the banana stem craft home industry has great potential in empowering women and improving the village economy.   Keywords: Women Empowerment, Home Industry, Banana Stem Craft.